Pengaruh Employee Stock Ownership Program (ESOP) terhadap Kinerja Bank Syariah Indonesia - Tri Hendrik (ITB AAS INDONESIA Surakarta, 2023)
and are involved in decision making. One of the compensations is the granting of shares or known as the Employee Stock Ownership Program (ESOP). The existence of ESOPs is expected to provide incentives for employees to increase productivity efforts. The application of ESOPs to performance is associated with agency theory where there is a contractual attachment between principals (shareholders/owners) and agents (management/employees). In this study, the research method used was paired sample t test. It was found that there was an effect of ESOP application on ROA and no effect of ESOP application on PBV.